2010
DOI: 10.1176/ps.2010.61.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Admission in First-Episode Psychosis: Developing a Risk Adjustment Model for Service Comparisons

Abstract: According to the C statistic estimates, the model developed provided good discrimination and was relatively robust in predicting hospitalization of first-episode psychosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Predicting inpatient hospitalization is difficult due to the complex interplay between systemic, clinical, and sociodemographic factors. Many studies have focused on patientrelevant risk factors of inpatient hospitalization, including severity of psychotic symptoms, substance use, suicidal behavior, and current manic symptoms (Addington et al, 2010;Gorwood, 2011;Hoblyn et al, 2009;Schubart et al, 2011;Sipos et al, 2001).…”
mentioning
confidence: 99%
“…Predicting inpatient hospitalization is difficult due to the complex interplay between systemic, clinical, and sociodemographic factors. Many studies have focused on patientrelevant risk factors of inpatient hospitalization, including severity of psychotic symptoms, substance use, suicidal behavior, and current manic symptoms (Addington et al, 2010;Gorwood, 2011;Hoblyn et al, 2009;Schubart et al, 2011;Sipos et al, 2001).…”
mentioning
confidence: 99%
“…Yet the preponderance of research shows that consumers of psychiatric services prefer having their own domicile over living with strangers who share their troubled histories (4). Shouldn't this play some role in considering what has gone wrong and what is going right (or at least going in the right direction)?…”
mentioning
confidence: 99%
“…The problem with mental health versions of abeyance is that, devised as stop-gap expediencies and assigned what many consider essential "dirty work" (3,4), their day-to-day operations tend to escape scrutiny and their effects (by design or default) go uninterrogated. So one might (as Padgett does) read "visible edifices" as "ironic commentary" on the industry's benighted view of social integration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that substance use at psychosis onset predicts poorer outcomes (Malla et al, 2008;Addington et al, 2010). We have used health system data for a population of 7.3 million persons to examine the risk of readmission in young people following a first admission for psychosis.…”
Section: Discussionmentioning
confidence: 99%